Electrical conductivity and initial water content of soybean seeds - Vieira, Roberval Daiton; Penariol, Adilson Luís; Perecin, Dilermando; Panobianco, Maristela (Pesquisa Agropecuaria Brasileira, 2002)
The initial seed water content can influence significantly the electrical conductivity results, and can make difficult the test standardization. The present work was carried out in order to study the effect of initial seed water content on the electrical conductivity results and to determine an equation to correct this influence. Six soybean cultivars were used, for two years, each cultivar having lots with high, medium and low seed vigor. Seed water content of each lot was adjusted to 7, 9, 11, 13, 15 and 17% before electrical conductivity test was run. The equation to correct the electrical conductivity values was calculated based on regression, including the two years data. The initial seed water content proved to be of high influence on the electrical conductivity interpretation and the equation is efficient to eliminate the effect of initial seed water content on the electrical conductivity data.